Effects of JPMR and listening to om chanting on attention and psychological states among university students: A randomized controlled trial - Nancy Jain; Ram Kumar Gupta (Wolters Kluwer Medknow Publications, 2024)
Background: Previously, both psychological and yogic relaxation techniques have shown a reduction in anxiety and also an improvement in cognition and mental health. In authors' knowledge, no study has been conducted to assess the immediate effects of the Jacobson Progressive Muscle Relaxation (JPMR) on attention and psychological states. Hence, the aim of the present study was to assess the immediate effects of the JPMR and listening to Om Chanting on the attention and psychological states, i.e,., (i) happiness, (ii) anger, (iii) emotional stability, and (iv) positivity among university students. Design: The research design used in this study is a randomized controlled design. Materials and Methods: In the present study, 90 university students with ages 1823 years (mean ± standard deviation: 21.5 ± 2.3 years) were randomized into three intervention groups, i.e,. JPMR, listening to Om Chanting and quiet sitting (QS) as a control group. The time duration for each intervention was 20 min. Each participant was assessed for (a) attention using six-letter cancellation test and (b) psychological states, i.e,. (i) happiness, (ii) anger, (iii) emotional stability, and (iv) positivity using the Visual Analog Scale, before and after all three interventions. Paired t-test was performed to compare before and after values of each variable of the participants. Results: Twenty-minute practice of JPMR improved psychological states such as (i) happiness (p < 0.05), (ii) emotional stability (p < 0.05), and (iii) positivity (p < 0.01). In addition, both attention and anger levels were reduced after 20 min of listening to Om Chanting (p < 0.01, respectively). In addition, QS reduced the attention level of the participants (p < 0.01). Conclusion: Findings of the present study suggest that the 20 min of practice of progressive muscle relaxation techniques as a psychological relaxation technique improves psychological states such as the levels of happiness, emotional stability, and positivity whereas 20 min of listening to Om Chanting showed a reduction in the scores of anger and attention.